Cross Platform Waste Reuse, Reduce And Recycle Management Application With Prototyping Methodology - Setiawan, Esther Irawati; Hartono, Patrick; Vu, Tong Nam Tuan; Halim, Kevin Jonathan; Ferdinandus, F. X.; Santoso, Joan (Depart. of Information Systems, FST, UIN Syarif Hidayatullah Jakarta, 2024)
The use of plastic bags by the public as containers for shopping goods is very high. People often throw away plastic waste carelessly, causing pollution everywhere. The biggest problem with the lack of recycling action lies in the lack of public awareness of the importance of implementing 3R (Reduce, Reuse, Recycle). People are less motivated to do 3R, one of which is because there are no rewards after doing 3R. This research develops an application provides rewards to the community for using Eco-Green Bags as an alternative to plastic bags. This research application has a system that makes it easier for people to carry out 3R. This proposed framework application uses the React Native framework for creating mobile apps and Next.JS for creating admin websites and APIs. With the React Native framework, application performance will be faster and smoother for users. The Next.JS framework allows developers to have a very clear project structure, because Next.JS uses file-based routing. With this research, it is hoped that people can be even more motivated to carry out 3R. The community can participate easily in implementing 3R without any coercion but through the community's own initiative. In this way, the application can be a real supporter of society in implementing 3R and avoiding the use of plastic bags which are also contributors to environmental pollution.